Literature review: Effects of Katuk Leaf (Sauropus androgynus L. Merr) on Breast Milk Increase - Farhana Fitri Amalia; Agung Ikhssani; Nurul Utami (POLTEKKES KEMENKES PONTIANAK, 2021)
Breast milk is considered the best form of nutrition for neonates and infants. The properties of breast milk facilitate the transition of life from in utero to ex utero. Breast milk provides a variety of bioactive substances for the developing baby during the early period of brain, immune and gut development. Katuk leaves (Sauropus androgni) are found very abundantly in Indonesia. People use S. androgyny as a traditional herbal medicine and are believed to have it to increase breast milk production. There are many publications that show the effect of lactagogum (an agent to increase milk production) of this plant. In several studies conducted there is evidence that the role of phytosterols and papaverine are two components that can increase the hormones prolactin and oxytocin. Scientific sources were obtained from Google Scholar and Pubmed in the form of textbooks and scientific journals totaling 24 units. Giving the extract resulted in a smoother circulation of the oxytocin hormone. The purpose of this literature review is to discuss the effect of S. androgynus which is believed to have a beneficial effect on breast milk production in and can be an agent of breast milk production in future research subjects.